The unknown player : accommodation behaviour in real-time strategy gaming communities - Müller-Braune, Frederic (2018)
Playing computer games is a hobby shared by many people of different national and cultural backgrounds worldwide. Therefore, it fits well as a testing ground for intercultural communication theory. This qualitative study applied the communication accommodation theory (Gallois & Giles, 2015) in a computer mediated gaming environment of the real time strategy game Company of Heroes. During the course of four weeks, a total of 44 datasets were collected in order to research: a) how players accommodate each other during interaction, b) how the game environment and structural framework influence players’ communication, c) how players construct an in-game identity, and finally, d) how players cope with the absence of physical and visual cues in a game. The data consists of pre-game and in-game chat logs and the researcher’s own notes concerning the situational in-game context. Analysis indicates that the communication accommodation theory is applicable in this new environment. However, some of its components are not fitting, are missing, or must be reinterpreted. The findings suggest that the accommodation behaviour is dependent on players’ displayed identity, player-to-player relationships and the scripts of play like e.g. game settings. In an environment, where players are not represented by a visual avatar, the identity cues shift from physical and visual towards imaginary ones such as pseudonyms or experience. Finally, this study shows that communication accommodation theory can also be applied in the context of computer mediated game communication, opening it to a whole new application environment.